Enhancing Disaster Resilience: Evaluating the Implementation of an Early Warning System through Table Top Exercises - Intan Permata Sari; Leylia Khairani; Rahmanita Ginting (Universitas Medan Area, 2023)
This research investigates the periodic implementation of an Early Warning System (EWS) using the Table Top Exercise (TTX) method to assess its effectiveness in enhancing community preparedness for disasters. Specifically, it analyzes the utilization of the Early Warning System as a disaster communication medium through the Table Top Exercise method and identifies challenges faced within the Disaster Risk Reduction Forum in Gung Pinto Village, Kec. Namanteran District, Karo. The study focuses on the People-Centered Early Warning System and the incorporation of Local Wisdom in the Early Warning System. The research employs the Knowledge Construction Theory as its theoretical framework. Data is gathered through interviews, observations, and document analysis, with qualitative analysis methods applied. The study concludes that the implementation of an Early Warning System (EWS) can significantly mitigate risks and safeguard communities against disaster impacts. Additionally, it highlights challenges such as limited information accessibility, resource constraints, and time limitations in the process.